PERSEPSI GEMBALA MENGENAI GEMBALA JEMAAT - Samuel Talahatu (Missio Ecclesiae, 2023)
The term "pastor" is popular in Christianity in general and the church in particular. In general, this term refers to someone who has the status of a priest. There are also differences in the understanding of this term among priests. Some agree more with the mention of pastors and there are also congregational pastors. The researcher wants to take the perception of pastors in the Pentecostal Church in Indonesia, the Kesamben congregation regarding "the pastor of the congregation". The aim is to gain knowledge about the perceptions of the priests on the subject. The research method used in this study is a descriptive method with a qualitative approach. The descriptive method is a research method that is used to describe problems that occur in the present or are ongoing, aiming to describe what should have happened when the research was carried out (Nana Sudjana and Ibrahim, 1989:64). From the results of the research it was found that the congregational pastor is someone who is chosen by God and is called to lead God's people through assignments to local church organizations. A pastor has great duties and responsibilities, namely always being close to the congregation, providing spiritual food, and helping them. The pastor must also always pray for the congregation, forbid the word of God and set an example at all times. Pastors also have to look for lost congregations or leave worship hours. Directing those who are lost on the right path, counseling troubled congregations, and also being able to be a good friend to get to know the congregation more closely. The pastor of the church also faces big challenges because of the requirements of the congregation with its multiple problems. Researchers also found ways to carry out shepherding duties, starting from establishing a vision and mission, creating a work program, recruiting support staff, and visiting and praying at any time.